Transformasi Ritual Syukuran dan Keselamatan Menjelang Kelahiran: Kajian Tradisi Meuri’ dalam Masyarakat Mandar Perspektif Urf' - Tualamsyah Wahab, Muh; Mansur, Rahmat; Aisyah, Nur (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
This research aims to explore the practice of the Meuri' Tradition in Acehnese society and analyze its relevance in the perspective of Islamic law. This tradition is a ritual of gratitude and a plea for safety for the mother and baby ahead of birth. The research was carried out through a qualitative approach with field research methods, and using normative-sharia and sociological approaches. The results showed that the Meuri' Tradition is generally carried out at seven to nine months of gestation and includes a series of religious and symbolic rituals, such as the recitation of Barzanji, joint prayers, as well as the use of traditional symbols such as bananas, free-range chicken eggs, silk sarongs, coconut oil, and incense. One of the typical processions is macceraq, which is the smearing of a mixture of chicken blood and lime on the forehead of pregnant women and the installation of burabeq as a form of protection. An analysis of this practice shows that the Meuri' Tradition does not contradict the principles of Islamic law, and even reflects the values of Maqasid al-Shariah, especially in preserving religion (al-din), soul (al-nafs), heredity (al-nasl), intellect (al-'aql), and property (al-mal). Thus, this tradition has significant cultural and spiritual value, while contributing to the preservation of local cultural identity within the framework of Islamic law.